Determinação de resíduos de agrotóxicos em mel empregando método QuEChERS modificado e GC-ECD - Orso, Débora (2011)
The production of honey has been increasing continuously in the world in function of the greatest consume of natural products. It is related directly to human health, and stimulated by its therapeutics and nutritious qualities. Due to this, it is necessary the verification of the features related to honey quality as: physical-chemical characteristics and identification of the floral and geographic origin of this product. For such intention emerges the importance of the residues analysis and monitoring to ensure its supply. In this study was developed and validated a method for the determination of 23 pesticide residues in honey using modified QuEChERS method and Gas Chromatography with Electron Capture Detection (GC-ECD). The fortification of honey samples was preformed, with a solution containing the 23 pesticides, in 3 levels of concentration (10.0; 20.0 and 50.0 μg kg-1), 6 extractions of each level was realized, and the modified QuEChERS method was applied. This extraction method consisted to weight 2.5 g of honey and the addiction of 5 mL of a Na2EDTA solution 0.1 mol L-1 and 5 mL of acetonitrile followed by vortex shaking, for 3 min. Partition consisted of the addiction of 6.0 g of anhydrous magnesium sulfate and 1.5 g of sodium chloride shaked for 1 min, followed by centrifugation for 8 min. The purification of the extract was realized through a dispersive clean up step in which 2 mL of the extract was transferred to another tube, previously added 120 mg anhydrous magnesium sulfate and 100 mg of primary secondary amine (PSA) followed by vortex shaking and centrifugation. Finally the extracts were analyzed by GC-ECD. The linearity of the analytical curves (6 levels of concentration and 6 injections of each level), detection limit (LOD), quantification limit (LOQ), matrix effects, accuracy and precision of the analytical method were evaluated. In general the linear range of the analytical curves prepared in acetonitrile and matrix matched were between 5.0 or 10.0 to 100 μg L-1 with values of r2 > 0.99. The GC-ECD technique enables the quantification of 95.6% of the compounds and method LOQ of 3.0 or 6.0 μg kg-1. Therefore, the method proved appropriated for pesticide multiresidue determination in honey, as well, effective purification technique for honey extracts combining good sensitivity and selectivity. All the parameters evaluated are in agreement to limits suggested for chromatographic methods validation.